(untitled) (Research, Society and Development, 2022)
Exposure to Hg has been extensively studied since the Minamata accident. Its deleterious effects were usually associated with the CNS, but recent research reveals this exposure as a possible risk factor for the development of heart diseases, such as systemic arterial hypertension. This review aims to evaluate a possible influence of chronic exposure to mercury in events of systemic arterial hypertension. This is a systematic review, using the Lilacs, PubMed and Scielo databases, with the use of keywords, and application of screening and eligibility criteria, as well as a filter in order to select publications from the last decade. The study identified 106 articles in different databases, where 6 of these were duplicates. In the screening and eligibility phase, 27 and 62 articles were excluded, respectively. Thus, only 11 articles were included for qualitative synthesis. Despite Hg being a heavy metal naturally present in the environment, professionals involved with mining and populations that have frequent fish consumption take the lead in this exposure, a fact demonstrated by the high levels of Hg in the capillary samples of these individuals. This chronic exposure causes severe imbalance to several biological systems, including the cardiovascular system, however, stating that this may be a driving force for the development of SAH may be wrong, and requires deeper and more detailed studies to be carried out on the subject.